Short-Term Intervention with Garlic-Based diets Modulates mRNA Expression of Calmodulin, Inositol-1,4,5-Trisphosphate Receptor-1, and Intracellular Adhesion Molecule in Cyclosporin-Induced Prehypertensive Wistar Rats - Ajayi; O.B.; Ajayi; O.O (Archives of Clinical and Biomedical Research, 2021)
This study assessed the short term effect of Allium sativum-based diets on mRNA expression of Calmodulin (CaM), Inositol Trisphosphate receptor (IP3R) and Intracellular adhesion molecule (ICAM-1) in the heart and aorta of cyclosporin-induced prehypertensive rats. Plasma levels of Ca2+ and Tumor Necrosis Factor-alpha (TNF-alpha) were also determined. The experimental rats used for this study were randomly allocated into 7 groups (n=4): normotensive control rats (fed basal diet); untreated prehypertensive rats (fed basal diet); prehypertensive rats (fed 10% and 20% Allium sativum based diets respectively); normotensive rats (fed 10% and 20% Allium sativum based diets respectively); prehypertensive rats treated with 10mg/kg captopril respectively for 7 days. Induction of hypertension with cyclosporin caused significant increase (p < 0.05) in mRNA expression of CaM, IP3R and ICAM-1, accompanied by increased (p < 0.05) systolic and diastolic blood pressures, plasma Tumor Necrosis Factor-alpha (TNF-alpha) and Ca2+ levels. These effects were considerably reversed by Allium sativum-based diets fed to the prehypertensive rats. These findings provide evidence which suggest that CaM, IP3R, and ICAM-1 are also upregulated in prehypertension, but are modulated by short term dietary intervention with garlic.